Role players and the negotiation process in the upgrading of squatter communities : a case study of Hout Bay - Van Wyk, Gabbi (Stellenbosch : Stellenbosch University, 2012)
Research project (M. in Town and Regional Planning) -- University of Stellenbosch, 1993.